Pengaruh Penggunaan Model Pembelajaran Inkuiri Terhadap Hasil Belajar PAI Siswa pada Masa Pandemi - Kidung Kinasih Cut Delpasya; Adi Rosadi; Dede Ridwan; Ridwan Agustian Nur (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The existing phenomenon is that the average learning outcomes of students have decreased. The purpose of this study is to determine the magnitude of the influence of the use of the inquiry learning model on the learning outcomes of class VIII students during the pandemic of PAI subjects. The method used is a descriptive method of analysis using a quantitative approach. The population of this study was 52 learners. While the sample was 34. The instruments used are questionnaires and tests. The data were analyzed by path analysis of significance levels α = 0.05. The research location was focused on SMP Islam Masagi Pasir Malang Sukabumi. This study found that the influence of the inquiry learning model on learning outcomes, namely with a figure of 0.338, shows that the amount of relationship is 34%. While the remaining 66% is caused by factors beyond changes in researcher variables This study concluded that there is an influence between the use of inquiry learning models on student learning outcomes by 34% and another 66% influenced by other factors